The COVID-19 Pandemic: Effects on Low- and Middle-Income Countries. (July 2020) - Bong, Choon-Looi; Brasher, Christopher; Chikumba, Edson; McDougall, Robert; Mellin-Olsen, Jannicke; Enright, Angela
Abstract : Coronavirus disease 2019 (COVID-19) is spreading rapidly around the world with devastating consequences on patients, health care workers, health systems, and economies. As it reaches low- and middle-income countries, its effects could be even more dire, because it will be difficult for them to respond aggressively to the pandemic. There is a great shortage of all health care providers, who will be at risk due to a lack of personal protection equipment. Social distancing will be almost impossible. The necessary resources to treat patients will be in short supply. The end result could be a catastrophic loss of life. A global effort will be required to support faltering economies and health care systems.